Optimizing Nitrogen Fixation and Recycling for Food Production in Regenerative Life Support Systems - Langenfeld, Noah J.; Kusuma, Paul; Wallentine, Tyler; Criddle, Craig S.; Seefeldt, Lance C.; Bugbee, Bruce (Frontiers in Astronomy and Space Sciences, 2021)
Nitrogen (N) recycling is essential for efficient food production in regenerative life support systems. Crew members with a high workload need 90–100 g of protein per person per day, which is about 14 g of N, or 1 mole of N, per person per day. Most of this N is excreted through urine with 85% as urea. Plants take up N predominantly as nitrate and ammonium, but direct uptake as urea is possible in small amounts. Efficient N recycling requires maintenance of pH of waste streams below about 7 to minimize the volatilization of N to ammonia. In aerobic reactors, continuous aerobic conditions are needed to minimize production and volatilization of nitrous oxide. N is not well recycled on Earth. The energy intensive Haber–Bosh process supplies most of the N for crop production in terrestrial agriculture. Bacterial fixation of dinitrogen to ammonium is also energy intensive. Recycling of N from plant and human waste streams is necessary to minimize the need for N fixation. Here we review approaches and potential for N fixation and recycling in regenerative life support systems. Initial estimates indicate that nearly all the N from human and plant waste streams can be recovered in forms usable for plants.